Investigating the Use of Open Air Burnt Sorghum and Wheat Straw Ashes to Soften Hard Water. - Bainomugisha, Jonan (Kabale University, 2023)
This study investigated the use of open air burnt sorghum and wheat straw ashes to soften hard water, three water samples that is sample A which was collected from a borehole at the camp of CICO-UNRA on Hoima Butiaba Wanseko road project located in Hoima District, B from a borehole in wanseko village - kigwera parish Bulisa District, and sample C from Koranorya borehole Ruk:ungiri District. These samples were tested to ascertain their initial properties, sample C was found to be with the highest hardness which was 740 mg/1 and was adopted to be used in the entire hardness removal experiment. It was then treated with different dosages of both SSA (sorghum straw ash) and WSA (wheat straw ash) starting from 2.5g and went on increasing uniformly by 2.5g until the maximum hardness removal efficiency of both ashes was reached i.e. where the further addition of ash did not change the hardness of water. It was observed that at a dosage of 20g/l, the hardness had been reduced to 348mg/l for WSA and at 22.5g, it had been reduced to 430mg/l for SSA. Further analysis on the treated water showed that the Color, TDS, Turbidity, PH and Alkalinity increased by 75%, 297%, 55%, 27.5% and 12% respectively for WSA at 20 grams of ash per liter of water and 75%, 306%, 90%, 29.5% and 17% respectively for sorghum straw ash at 22.5g/l. All these parameters were increased but remained within the acceptable Ugandan standard limits for portable water except for the alkalinity which still increased beyond the standard maximum of 500mg/l much as the initial results on the sample before addition of the ashes was at 576 which was still beyond the standard. Finally, WSA demonstrated the highest hardness removal efficiency of 53% at a dosage of 20g/l than SSA that reduced it by 42% at a dosage of 22.5 g/1.